The Effect of a Novel Video Game on Young Soccer Players' Sports Performance and Attention: Randomized Controlled Trial - Adrian Feria-Madueño; Germán Monterrubio-Fernández; Jesus Mateo Cortes; Angel Carnero-Diaz (JMIR Publications, 2024)
Abstract BackgroundCurrently, the fusion of technology and sports is inevitable. The integration of various systems and devices has brought about significant transformations in established sports practices, impacting not only the rules but also physiological, biomechanical, and even psychological aspects. ObjectiveThe purpose of this study was to analyze the effect of an attention intervention through a video game on young soccer players. MethodsTwelve young male soccer players (age: mean 8.5, SD 1 years) were divided into 2 groups: a control group (CG; n=10) and an experimental group (EG; n=10). During the 6-week training program, the EG received attention training through a video game twice a week for 15 minutes per session. Pre- and postintervention measurements included a specific decision-making soccer test and interviews with coaching staff. Additionally, success in the video game, muscular activity, and sweat levels were monitored. ResultsThe EG demonstrated a significant improvement in video game success following the intervention program, as indicated by the achieved level (PPP ConclusionsOur findings reveal that incorporating a specific attentional video game into a soccer training program enhances decision-making compared to a program without the video game. Therefore, it is advisable for practitioners to consider using this tool due to its high efficiency in terms of economic and temporal costs, particularly in improving a key psychological variable.